Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 9 - Review Exercises - Page 691: 2


$x=-3; y=-3$

Work Step by Step

We need to solve for $x$ by subtracting $y$ from both sides. $x-y=0 \implies x=y ...(1)$ Now, plug the value of $x$ into the second equation. $2(y)-3y=3 \implies y=-3$ We will plug the value of $y$ into the first equation, giving: $x=-3$ Thus, $x=-3; y=-3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.